CARA PEMBUATAN PUPUK KOMPOS BERBAHAN DASAR KOTORAN SAPI - Daffa, Ady Ahmad; Astuti, Mustika Fuji; Parastining, Sesilia Novia Ayu; Safitri, Ajeng Aissah; Alvian, Alvian; Rahmawati, Mila; Anaputri, Lesi; Aranta, Muhammad Antony; Ramdani, Suri; Rahayu, Susan (Universitas Mataram, 2024)
Making organic fertilizer based on cow dung as an environmentally friendly alternative for modern agriculture. The organic fertilizer produced not only functions to increase fertility land, but also helps manage waste and protect the environment. Making process Fertilizer involves several important stages, such as preventing ingredients, mixing, controlling humidity, aeration and cooling. Studies conducted show that organic fertilizers The resulting product contains good nutrients, provides physical, chemical and chemical improvements biology in soil. This product supports sustainable agricultural practices as well as produce healthier food.